Measuring Satisfaction of Users from e-Library vis-à-vis selected Libraries of Rajasthan states - Sahu, Prabha; Pandey, Shri Ram (Library Waves, 2018)
Emergence of E-resources has caused a shift in user’s perception also. In the changing dimensions, it does not matter what you have but the important issue is to have an access to it. Today, we can have seamless access to any information from anywhere anytime crossing all the geographical boundaries, provided basic infra-structure is available. All those developments are leading to the emergence of digital libraries or electronic libraries in a parallel way. In the present scenario, users are seeking a one-stop shop to satisfy their information needs. This study was conducted in the libraries of Rajasthan. For this purpose the data from 230 respondents of 10 libraries was collected and analyzed with one sample t-test and multiple regression analysis. Study revealed that respondents believed that the variety of e-resources available in libraries are significant and E-Book, Database and E-Journals are the major benefits of E-libraries in Rajasthan state.